Indigenizing the English Language - Dela Cruz, Luvizminda (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
This preliminary study is a description of the syntactic features of formal written Philippine English using 19 graduate term papers as corpus of the analysis. The features found to be distinctive of the corpus are the following: the unusual application of congruence rules, both subject-predicate and pronoun antecedent, the reclassification of lexical items, including the transitive-intransitive distinction and the mass-count distinction, the simplication of tense/aspect usage, the unusual use of adjectives and adverbs, the unusual word order involving the object of the verb or the adverb and the unusual use of lexical items. The study serves as database for further investigations into the forms of the evolving Philippine English that have become standardized or are on their way to becoming standardize.